Role of synbiotics in reducing postoperative infections in patients with hip fracture: pilot study: Vloga sinbiotikov v zmanjšanju okužb po operacijah zloma v predelu kolčnega sklepa: pilotska študija - Pevec, Teodor (Acta Medico-Biotechnica, 2021)
Purpose: Despite the development of surgical methods, infections continue to be serious postoperative complications. Probiotics have been shown to be effective in reducing the prevalence of infections. We explored the effectiveness of probiotics in reducing the prevalence of infections in subjects undergoing surgery for hip fractures.Methods: Fifty-one patients admitted for surgical treatment of hip fractures were divided randomly into two groups: Synbiotic 2000 Forte and placebo. The occurrence of infection was closely observed upon hospital admission until the fifth postoperative day using, among other parameters, the C-reactive protein (CRP) level. Additionally, the patients’ tolerance to Synbiotic 2000 Forte was established using subjective (self-reported problems) and objective means.Results: Infection was confirmed in 4 patients in each group. Urinary tract infection was noted in 7 subjects and a local wound infection in 1 patient. No differences were found in CRP levels upon hospital admission and the fifth postoperative day. Tolerance to Synbiotic 2000 Forte was lower in patients undergoing placebo treatment.Conclusion: Synbiotic 2000 Forte did not reduce the number of postoperative infections. Further studies are needed to confirm these findings.
Keywords: hip fracture; infection; symbiotic; Synbiotic